2011
DOI: 10.3109/02713683.2010.549601
|View full text |Cite
|
Sign up to set email alerts
|

NBHA Reduces Acrolein-Induced Changes in ARPE-19 Cells: Possible Involvement of TGFβ

Abstract: Purpose Acrolein, a toxic, reactive aldehyde formed metabolically and environmentally, has been implicated in the damage to and dysfunction of the retinal pigment epithelium (RPE) that accompanies age-related macular degeneration (AMD). Our purpose was to investigate the potential of acrolein to influence the release of transforming growth factor beta-2 (TGFβ2) and vascular endothelial growth factor (VEGF), to assess the ability of N-benzylhydroxylamine (NBHA) to prevent the effect of acrolein on cytokine rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Furthermore, we found that acrolein increased levels of VEGF and TGFβ2 in the cell media of ARPE-19 cells, that the increase of TGFβ2 could be partially blocked by NBHA, and the increase in VEGF could be partially blocked by NBHA and the TGFβ pathway blocker SIS3 supporting the hypothesis that acrolein exerts its effects through modulation of the TGFβ pathway. 29 We now demonstrate that acrolein has a greater effect on reducing ARPE-19 cells in higher than in normal glucose levels and that this reduction in cell number can be modulated by co-administration of NBHA (sequestering the acrolein) which reduced the effects of the glucose concentration difference in cell viability. This is most likely due to the enhanced oxidizing effect of the higher glucose levels and is not unexpected considering the increased mitochondrial potential associated with hyperglycemia as evidenced by the work of Du et al 55 and Brownlee et al 56 Acrolein disrupted TGFβ and VEGF regulation by the remaining cells, causing each cell to contribute more of each cytokine to the CM, and this, too, could be mitigated by co-treatment with NBHA.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, we found that acrolein increased levels of VEGF and TGFβ2 in the cell media of ARPE-19 cells, that the increase of TGFβ2 could be partially blocked by NBHA, and the increase in VEGF could be partially blocked by NBHA and the TGFβ pathway blocker SIS3 supporting the hypothesis that acrolein exerts its effects through modulation of the TGFβ pathway. 29 We now demonstrate that acrolein has a greater effect on reducing ARPE-19 cells in higher than in normal glucose levels and that this reduction in cell number can be modulated by co-administration of NBHA (sequestering the acrolein) which reduced the effects of the glucose concentration difference in cell viability. This is most likely due to the enhanced oxidizing effect of the higher glucose levels and is not unexpected considering the increased mitochondrial potential associated with hyperglycemia as evidenced by the work of Du et al 55 and Brownlee et al 56 Acrolein disrupted TGFβ and VEGF regulation by the remaining cells, causing each cell to contribute more of each cytokine to the CM, and this, too, could be mitigated by co-treatment with NBHA.…”
Section: Discussionmentioning
confidence: 63%
“…28 Our previous studies in normal glucose conditions concluded that NBHA and SIS3 are capable of reducing acrolein-mediated RPE cell death. 29 We also reported that the action of acrolein in the reduction of cell viability and the increase of VEGF are partially mediated by TGFβ2. 29 Acrolein, itself, though associated with diabetes complications and retinal degeneration in age-related macular degeneration has not been studied in the eyes of subjects with diabetes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…An over accumulation of glucose and/or fructose damages blood capillaries in the retina with fluid and lipids leakage to the macula, the region of the retina with high visual acuity. The fluid accumulation results in the swelling (or edema) of the macula, which blurs vision [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we determined the involvement of acrolein and examined two putative acrolein scavengers, a thiol compound cysteamine (CystE) and a hydroxylamine N -benzylhydroxylamine (NBHA), to identify novel therapeutic options for liver injury [17, 19]. Thiol and hydroxylamine trap aldehyde and decrease its toxicity [18].…”
mentioning
confidence: 99%